THYROID STORM WITH ACUTE PLACCID QUARIPARESIS DUE TO THYROTOXIC MYOPATHY - HC, Tee; JH, Ho; SK, Serena Khoo; YK, Fung (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Severe thyrotoxicosis is known to cause myopathy, but is rarely associated with acute flaccid quadriparesis. It is imperative to distinguish this from other potentially lifethreatening conditions such as Guillain-Barré syndrome, myasthenia gravis and hypokalemic periodic paralysis that may present with similar clinical features. We report a case of thyroid storm presenting with acute flaccid paralysis. CASE A 25-year-old lady was diagnosed with Graves’ disease one year ago but was poorly compliant to antithyroid drugs. She presented with 3 days’ history of fever and rapidly progressive generalised body and limb weakness rendering her bedridden. Neurologic examination identified flaccid quadriparesis with areflexia and intact sensation. She was agitated, febrile, tachycardic with atrial fibrillation in failure and was diagnosed with thyroid storm with Burch and Wartofsky score of 60. Her thyroid stimulating hormone level was <0.01 mIU/L and free thyroxine was 43.56 pmol/L. Serum electrolytes and creatinine kinase were normal, and type 2 respiratory failure was not demonstrated. Other investigations were unremarkable including viral serology, autoimmune markers and antiganglioside antibodies. Her nerve conduction study and electromyography were suggestive of generalized myopathy without neuromuscular junction abnormalities. She was intubated, ventilated and commenced on hydrocortisone, Lugol’s iodine, propylthiouracil, cholestyramine and propranolol, resulting in marked clinical improvement and normalisation of thyroid function in 7 days. Total thyroidectomy was done before discharge as definitive treatment. She regained muscle power and function gradually over months following biochemical remission. CONCLUSION Acute thyrotoxic-induced myopathy should be considered in uncontrolled thyrotoxicosis presenting with flaccid quadriparesis. Contributing features may include increased cellular metabolism and energy utilisation, increased catabolism and protein degradation, and inefficient energy utilisation. Early definitive therapy with radioactive iodine or thyroidectomy is crucial in achieving rapid biochemical control, preventing future occurrence of acute thyrotoxic induced myopathy, and improving muscle recovery.